PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA DEDICADA A LA PRODUCCIÓN Y COMERCIALIZACIÓN DE CARAMELOS A BASE DE PANELA CON SABOR A CHOCOLATE Y LIMÓN EN LA CIUDAD DE LOJA - Macas Angamarca, Fátima Rosalía (2019)
The present research work called “Feasibility project for the creation of a company dedicated to the production and marketing of chocolate-lemon and lemon-flavored candies in the city of Loja”, was executed in the city of Loja with the purpose of generating sources of employment in terms of the development of the productive and commercial sector, using locally made products together with the use of appropriate strategies to boost the growth of the city of Loja. Therefore, the general objective of: developing a feasibility project to determine the creation of a company producing and selling candies based on chocolate and lemon flavored candies in the city of Loja was met. Thus, for the development of this work, four specific objectives were raised that are linked to the four studies that the project will contain, such as the market study, technical study, financial study and financial evaluation, these studies will determine the feasibility of the project . Likewise, for the elaboration of the project the methods were used: deductive, inductive and analytical, in addition to techniques such as: bibliographic compilation and surveys, where a sample of 381 surveys applied in the city of Loja was determined, allowing to determine tastes and people's preferences. With the information from the surveys, it was obtained that in the city of Loja, there is an unsatisfied demand for 1,582,781 candy covers, a marketing plan was developed to introduce the new product to the market and position itself in the local families; As for the technical study, the location was determined, which is in the La Tebaida neighborhood; The project has an installed production 5 capacity of 236,520 cases of panela candies and a used capacity of 56,160 cases of panela candies, the same that the company will keep producing for 5 years of the project. An administrative study was carried out, where the company was established, as a sole proprietorship of limited liability, the organizational charts and manuals of functions necessary for the operation of the company were prepared. In the financial study, the total investment was determined, which amounts to $ 8,476.18, this investment is paid by 53% of its own and 47% through a financial loan granted by BANECUADOR. In the financial evaluation, the feasibility of the project was verified since favorable results were obtained in the indicators such as: the NPV that results in $ 10,799.71; the IRR is 62.14%; the RBC is 0.26 cents and the PRC is 1 Year, 5 Months and 19 Days. The sensitivity analysis shows that the project can support a cost increase of up to 14.66% and a decrease in revenue of 11.62%. And finally we have the respective conclusions and recommendations of the Project.